INTERNATIONALIZATION OF HIGHER EDUCATION: POLICY AND MANAGEMENT CHALLENGES IN CENTRAL ASIA - Ergasheva Ozodabonu Bahodirjon qizi (ILMIY YANGILIKLAR VA INTELLEKTUAL TADQIQOTLAR, 2025)
Abstract: The internationalization of higher education is an increasingly important agenda in global academic systems. Central Asian countries, including Uzbekistan, Kazakhstan, Kyrgyzstan, Tajikistan, and Turkmenistan, have been actively pursuing reforms to align their higher education systems with international standards. This article explores key policy and management challenges facing the internationalization process in Central Asia, including governance, quality assurance, mobility programs, language barriers, and institutional capacity. Drawing on regional policy analysis and case studies, it provides recommendations for building sustainable and inclusive internationalization strategies.